Whole-brain mapping of afferent projections to the suprachiasmatic nucleus of the tree shrew. (December 2021) - Ni, Rong-Jun; Shu, Yu-Mian; Luo, Peng-Hao; Zhou, Jiang-Ning
Highlights: Distribution of the vasoactive intestinal peptide in the SCN of tree shrews. The first detailed whole-brain mapping of inputs to the SCN in tree shrews. The SCN-projecting regions were firstly identified in the tree shrew brain. Density of SCN-projecting neurons throughout the tree shrew brain was analyzed. Abstract: The suprachiasmatic nucleus (SCN) is essential for the neural control of mammalian circadian timing system. The circadian activity of the SCN is modulated by its afferent projections. In the present study, we examine neuroanatomical characteristics and afferent projections of the SCN in the tree shrew (Tupaia belangeri chinensis) using immunocytochemistry and retrograde tracer Fluoro-Gold (FG). Distribution of the vasoactive intestinal peptide was present in the SCN from rostral to caudal, especially concentrated in its ventral part. FG-labeled neurons were observed in the lateral septal nucleus, septofimbrial nucleus, paraventricular thalamic nucleus, posterior hypothalamic nucleus, posterior complex of the thalamus, ventral subiculum, rostral linear nucleus of the raphe, periaqueductal gray, mesencephalic reticular formation, dorsal raphe nucleus, pedunculopontine tegmental nucleus, medial parabrachial nucleus, locus coeruleus, parvicellular reticular nucleus, intermediate reticular nucleus, and ventrolateral reticular nucleus. In summary, the morphology of the SCN in tree shrews is described from rostral to caudal. In addition, our data demonstrate for the first time that the SCN in tree shrews receives inputs from numerous brain regions in the telencephalon, diencephalon, mesencephalon, metencephalon, and myelencephalon. This comprehensive knowledge of the afferent projections of the SCN in tree shrews provides further insights into the neural organization and physiological processes of circadian rhythms.